The ACFTU and Chinese industrial relations - Ma, Zhining (Frankfurt am Main, 2011)
"In the context of China's growing influence over the global economy, its newly developed labour market and the subsequent series of industrial relations issues have captured much attention. However, research on industrial relations and labour problems in China is relatively underdeveloped. The classic three-party industrial relations model, which was developed for western economies, has been difficult to apply to China's circumstances. In light of this, this book reviews the relevant existing industrial relations theories and explores their applicability to China. It then proposes a new six-party taxonomy for the analysis of China's union system and industrial relations, taking into account distinctive industrial relations actors with 'Chinese characteristics' and their interrelationships at different social levels. This new taxonomy is then used to provide a broader picture of evolving industrial relations in China. "